The Distribution of Precious and Energy-Critical Elements at the Scale of a Porphyry Copper Deposit - BRODBECK, MAURICE (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2020)
Magmatic-hydrothermal porphyry copper deposits are the world's primary sources of Cu. Moreover, these may contain extractable concentrations of rare metal(loid)s e.g., Se, Te, In, Co, Ge, Ga, Ag, Au and Re. Some of these elements are classified as energy critical elements, whose shortage is considered a limiting factor for emerging energy technologies; diversifying their supply is critical. Porphyry copper deposits (PCDs) are mined at low grades, but vast tonnages. Hence, even low concentrations of by-product elements can represent a significant resource. However, the deportment of ECEs and precious metals in Cu ores, their distribution at the mineral- and orebody-scale is poorly understood in most PCDs. This lack of information limits the effective recovery of rare metal(loid)s and causes an unnecessary waste of resources. This situation can be remedied with element deportment studies; by informing geometallurgy, economic and ecologic benefits can be promoted in the form of improving recovery, adding value to ore resources and helping to reduce the dispersion of deleterious metal(loid)s into the environment. This is the motivation for the current research project. A fundamental aim of this study is to determine and compare the ECE and precious metal inventory of copper ores from four different porphyry Cu systems to identify deposits of high rare metal(loid) potentials; these are Quebrada Blanca, La Fortuna and Relincho in Chile, and Bingham Canyon (USA). Additionally, internal zonation within the orebodies and processes leading to enrichment and secondary redistribution of ECEs and precious metals are investigated. These objectives are addressed with: characterising ore mineral species (SEM-EDS); analysing their trace element contents (LA-ICP-MS); determining the nature of trace element residence in their host minerals; quantification of major and minor ore minerals; visualising the trace element partitioning between complex mineral textures, and advancing the relevant micro-analytical techniques (LA-ICP-MS mapping). Element deportment results show that bornite (Cu5FeS4), chalcopyrite (CuFeS2) and pyrite (FeS2) are the most common primary hydrothermal sulphide minerals in Cu ores from the four PCDs. The highest by-product potentials were found for Se, Ag, In, Te, Au and Bi; contents of other ECEs (Co, Ge and Ga) are negligible. Bornite is the main host for Se, Ag, Te and Bi, and chalcopyrite for In. Discrete native gold and electrum grains, as well as Ag-telluride minerals contribute to the overall deportment of Au, Ag and Te. Primary Cu-(Fe) sulphides from La Fortuna deviate most prominently from the other three deposits, with distinctly lower Ag and Bi, but the highest Au and In contents. Copper sulphides from the three remaining PCDs show similar contents in potential by-product elements; but respectively highest concentrations were recorded for the following deposits: Bingham (Se); Quebrada Blanca (Ag, Bi); and Relincho (Te). Two-dimensional trace element maps (by LA-ICP-MS) of complex textures revealed that secondary processes can promote the redistribution of rare metal(loids) at various scales. Firstly, digenite (Cu9S8) exsolution within bornite during the late cooling stages of the hydrothermal system at Bingham led to characteristic partitioning of precious metals and Te into digenite. Secondly, at Quebrada Blanca downward-propagating supergene weathering fluids induced the replacement of chalcopyrite by chalcocite (Cu2S) and thereby introduced elevated precious metal contents. The resulting complex deportment has potential implications for geometallurgy. Lastly, the La Fortuna and Relincho deposits are only 40 km apart but show very different metal(loid) endowments; copper ore from La Fortuna bears high Au contents, and from Relincho high Mo, Ag and Te contents. Findings suggest that this divergence in credit element enrichment is likely related to the exsolution of mineralising fluids at relatively shallow depth at La Fortuna (<3 km), compared to Relincho (>3 km).
APPROVED
Keywords: Critical Raw Materials; Copper Deposits; LA-ICP-MS; Micro-analytics